Effectiveness of a musical-based learning approach on knowledge and happy index related to anatomy syllabus: a quasi-experimental pilot study - Minhat, Halimatus Sakdiah; Abas, Razif; Zakariah, Siti Zulaikha; Ibrahim, Rosni; Mohamed Razali, Camellia Siti Maya; Salleh, Marzelan (Universiti Putra Malaysia Press, 2023)
Introduction: Musical-based education has been linked with improved students’ academic performance and mental wellbeing. This study aimed to evaluate a musical-based anatomy learning module using the combination of music, choreographed movements and 3D anatomy illustrations on muscles of the hand. Methods: A 5-minute duration video on muscles of the hand was developed through series of discussions with expert panels to incorporate the three stated components, emphasizing on the use of catchy music and simple terms to assist memorization skills. A single arm quasi-experimental pilot study was conducted with pre- and post-intervention measurement of knowledge, perception, stress and happy index related to learning anatomy. A total of 157 medical students were recruited and exposed to a total of 20 minutes video duration over three days. The effectiveness of the intervention was investigated using paired t-test and was interpreted based on the pre- and post-measured exposure mean differences. Results: The newly developed musical-based anatomy learning module had effectively improved knowledge and happy index related to learning anatomy, with significant mean differences were observed on the total mean scores for knowledge (MD= 2.707, p< 0.001) and happy index (MD=3.256, p< 0.001), as well as significant reduction of the mean scores for the negative items for perceptions and stress. Conclusion: The improved knowledge and happy index related to learning anatomy reflecting the positive impact of music used in combination choreographed movements and 3D illustrations to strengthen memorizing skills of medical students as well as instilling positive mood.